2018
DOI: 10.1002/cncr.31102
|View full text |Cite
|
Sign up to set email alerts
|

Moving toward a true depiction of tobacco behavior among Asian Indians in California: Prevalence and factors associated with cultural smokeless tobacco product use

Abstract: BACKGROUND: Asian Indians (AIs) in the United States exhibit disproportionate burdens of oral cancer and cardiovascular disease, which are potentially linked to smokeless tobacco. However, little is known about the use of cultural smokeless tobacco (CST) products in this population. METHODS: California Asian Indian Tobacco Use Survey data from 2004 (n 5 1618) were used to investigate CST prevalence among California's AIs. CST products included paan, paan masala, and gutka. A multivariable logistic regression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…These practices were popular across almost all age groups and generations [21,22,27,45] with various patterns of practices in different religions [25,29,44]. Of concern was the supportive role of family and friends in the initiation of this kind of practices [22,26,27,42,43]. These findings complement the recent WHO report [57] regarding trends of tobacco product use in the South-East Asia region.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…These practices were popular across almost all age groups and generations [21,22,27,45] with various patterns of practices in different religions [25,29,44]. Of concern was the supportive role of family and friends in the initiation of this kind of practices [22,26,27,42,43]. These findings complement the recent WHO report [57] regarding trends of tobacco product use in the South-East Asia region.…”
Section: Discussionmentioning
confidence: 59%
“…This is the first integrative review to assess current evidence regarding the knowledge, attitudes, and practices of South Asian immigrants in relation to oral cancer risk in developed countries. The majority of studies were conducted in the USA [21,22,40,42,43] and UK [25, 27-29, 41, 44, 45], and more recently in Italy [14] reflecting the changing migratory patterns of South Asians. It is also evident from the diversity of populations studied that irrespective of native countries, the oral cancer risk behaviours are widespread across a broader age range, gender, generations, and social class.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were also notable age variations when the risk habits were initiated in their home countries ranging from 3-18 years [20,21,26,39]. Various reasons were cited behind the initiation of these practices such as social networks made up of South Asian friends or co-workers (45%-48.2%), passing of habit from one generation to the next (3.3%-81%), observation and encouragement within family members (27.5%-81%) [21,25,26,38,43]. These findings were also reflected in the qualitative studies [20,22,41] A pilot study [21] in the USA revealed that immigration can also influence the patterns of risk practices with participants switching habits from pan chewing to guthka use (nearly 54%) due to the social unacceptability of the former and ease of procurement /storage of the latter.…”
Section: Every Third Person Inmentioning
confidence: 99%
“…Supporting this notion is a study in the USA that found that people preferred smoking and sometimes swallowing the tobacco/pan instead of spitting it out because of society finding this inappropriate [20]. However, some studies found that betel quid usage along with tobacco chewing/smoking was an integral part of lifestyles, deeply rooted in the culture of south Asians and that these practices simply continued in new settlements as a habit or addiction [25,26,38,41,43].…”
Section: Every Third Person Inmentioning
confidence: 99%